Freeze-Thaw Resistance of Normal and High Strength Concretes Produced with Fly Ash and Silica Fume - Cenk Karakurt; Yıldırım Bayazıt (Advances in Materials Science and Engineering)
This study is based on determination of the freeze-thaw resistance of air-entrained and non-air-entrained normal strength concrete (NC) and high strength concrete (HSC) produced with fly ash and silica fume according to surface scaling. The procedure allows us to measure the amount of scaling per unit surface area due to a number of well defined freezing and thawing cycles in the presence of deicing salt. The weight loss, surface scaling, moisture uptake, and internal damage were measured after 0 and after every 4th freeze-thaw cycle. The test results showed that the freeze-thaw resistance is influenced directly by the compressive strength property of the concrete. Silica fume significantly reduced the resistance of normal strength concrete against freeze-thaw effect without plasticizing agent. The surface scaling of silica fume concrete without admixture was 22% higher than reference normal concrete.